Tumour cell population growth inhibition and cell death induction of functionalized 6‐aminoquinolone derivatives. (December 2015) - Franci, G.; Manfroni, G.; Cannalire, R.; Felicetti, T.; Tabarrini, O.; Salvato, A.; Barreca, M. L.; Altucci, L.; Cecchetti, V.
Abstract: Objectives: A number of previous studies has provided evidence that the well‐known anti‐bacterial quinolones may have potential as anti‐cancer drugs. The aim of this study was to evaluate potential anti‐tumour activity and selectivity of a set of 6‐aminoquinolones showing some chemical similarity to naphthyridone derivativeCX‐5461, recently described as innovative anti‐cancer agent. Materials and methods: In‐house quinolones1‐8 and ad hoc synthesized derivatives9‐13 were tested on Michigan Cancer Foundation‐7 (MCF‐7) breast cancer cells and mesenchymal progenitor (MePR2B) cell lines, analysing their effects on the cell cycle and cell death using FACS methodology. Activation of p53 was evaluated by western blotting. Results: Benzyl esters4, 5 and their amide counterparts12, 13 drastically modulated MCF‐7 cell cycles inducing DNA fragmentation and cell death, thus proving to be potential anti‐tumour compounds. When assayed in non‐tumour MePR2B cells, compounds4 and5 were cytotoxic while12 and13 had a certain degree of selectivity, with compound12 emerging as the most promising. Western blot analysis revealed that severe p53‐K382ac activation was promoted by benzylester5 . In contrast, amide12 exerted only a moderate effect which was, however, comparable to that of suberoylanilide hydoxamic acid (SAHA). Conclusions: Taken together, these results further reinforce evidence that quinolones have potential as anti‐cancer agents. Future work will be focused on understanding compound12 mechanisms of action, and to obtain more potent and selective compounds.